Digital Marketing Strategy Formulation For Distributor-Based Company Using Digital Customer Journey Approach (Study Case: PT Barca Trios Chemindo) - Naufal Afaf; Neneng Nurlaela Arief; Iwan Setiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research objectives is to identify critical touchpoint (s) of digital customer journey in PT BTC marketplace channel strategy, to discover the result of current PT BTC digital customer journey feedback, to give recommendation in digital marketing strategy to improve PT BTC digital customer journey, and to give supporting strategy to enhance PT. In this research, data collection methods will be using qualitative data from Primary Data and Secondary Data. This research found 5 critical touchpoints of digital customer journey in PT BTC marketplace channel strategy, like Awareness, Appeal, Ask, Act, Advocate. Current marketplace channel strategy is effective to catch new B2B customers but less effective to retain their consistency to buy via online transaction. From this finding research, the best suitable digital marketing strategy that fit to PT BTC customer journey is creating and establishing website and improving its system to become modify-website that enabled to e-commerce facilities. The supporting strategy to establishing website marketing strategy is purposing new company’s marketing division structure to delegate workload better, more effective and more efficient.